Ecological problems of geotechnology; IFOST 2012; Vol. 1 - Spirin E. K. Eduard Konstantinovich (Section 1. Chemical engineering and "Green technology", 2012)
The given article considers the ecological problems of the geotechnological method of metal extraction from crude ore. The author also discusses the problem of further development of the geotechnological method with a view to low-waste processes and reduction of valuable components waste.